O racismo institucional e o acesso aos serviços de saúde: experiências de Quilombolas - Santos, Auriene Rodrigues (Universidade Federal do Tocantins, 2024)
The aim of this study was to understand the experiences of quilombolas regarding access to health services offered by the Unified Health System (SUS). This is a qualitative, exploratory study using field research. The instrument used was a semi-structured interview based on a 8-question script, accompanied by a questionnaire aimed at collecting the sociodemographic profile of the participants. We worked with a sample of 2 participants who were over 18 and associated with quilombola communities. To process the data, the Interpretation of Meanings Method was used, anchored in a hermeneutic-dialectic perspective, with the aim of achieving an analytical description. This method is based on the following stages: 1) Transcribing and typing the recordings of the individual interviews; 2) Assigning codes to the interviewees and the people they mentioned; 3) Intensive and comprehensive reading of the transcribed texts. At the end, thematic axes were drawn up with the central ideas present in the participant's narrative, which were discussed from an intersectional perspective, using standard authors in this field such as Silvio Almeida, Mbembe, Fanon, Kilomba, Gonzales, Angela Davis, Akotirene and Foucault. Based on the interviews, the results were systematized into the following thematic axes: I) Quilombola health care: ancestral knowledge as the first option; II) Experiences and challenges in accessing the Health Care Network; III) Institutional Racism and its effects on the health of the black population and IV) The color of pain: Racism and Mental Health. It was concluded that the expression of Institutional Racism imposes barriers to access to health care for members of quilombola communities and the black population insofar as the actions and services of the RAS do not recognize the socio-cultural specificities of this population and do not use racialized devices in health care. It was found that although there has been progress in the implementation of public policies that consider race as a determinant of health, there are obstacles to their effective implementation.